O que a história ensina sobre as epidemias no Brasil? Orientações didáticas para o ensino fundamental - Costa, Leandro Garcia (2021)
This research aims to develop didactic guidelines for teaching the history of diseases in Elementary School through a bibliographic list and analysis of textbooks that make up the National Textbook Plan, the PNLD of the year 2019. The analysis proposed by this the dissertation focuses on the history books of the 7th, 8th and 9th grades of elementary school, in which the incidence, even if incipient, of thematic approaches to diseases through historical narratives focused on the history of Brazil was verified. The analysis of textbooks allowed the composition of a database, providing an understanding of the diseases and epidemics that plagued Brazil over time. This history of diseases in the history of Brazil, fostered the composition of the propositional part, consisting of didactic guidelines that will help teachers and students in teaching the subject in history classes. It was also investigated how the history of diseases appears in national curricula, such as the National Curriculum Base (BNCC), National Curriculum Parameters (PCNs) and the Curriculum Document of Goiás (DC/GO), in order to understand how these resume influence directly in the composition of textbooks present in the National Textbook Program for public schools throughout Brazil. In the discussions on the history of diseases and in the preparation of didactic guidelines, an analysis of Covid-19 was included, paying attention to its impacts on contemporary Brazilian society.